อัตลักษณ์ไทยในการอบรมเลี้ยงดูเด็กเรื่องมารยาททางวาจา - Boonprasert, Pimpaporn (Asian Health, Science and Technology Reports, 2011)
This research is a qualitative research. There are two main aims in this research Firstly, it tends to analyze the manner concept in speaking of Thailand by comparison with the teachings of Buddhism and to analyze the relationship between the verbal concepts towards sufficiency. The research taken the samples from literary “sombut of phudi” (property of gentleman), which considered important and strongly related to the knowledge of Thai manner. According to the study, the research found that people who are “phudi” (gentleman) must communicate consideration issues; to maintain the face, clear, disclosure,do not show that the selfish, to respect the receiver, give as beauty word to speak or use rethoric. A bad way verbal and in fact consistent with concept in Buddhism described the story of good due to said that based on the story which sorted the priority is the basis of “truth is correct”, straightforward and clarity. Basis of beauty is sonorousness sweet has to say and basics of “calm words are spoken”. Not speak babble or exaggeration necessary esxplorer implicates note of conflicting upset or create dissatisfaction, with others in society. Training and teaching this subject right given culture since his behaviour should behave in practice that lead to recognize their estimated reasonable article is diaparage on the moderation have merit decision and actions consistent with the philosophy of sufficient critical philosophy is to help people are together peace. To regard countries passed a critical sustainable.